Anodic adsorptive stripping voltammetric determination of atrazine in spiked soil samples with a gold microelectrode - Morais, Simone (2013)
Microwave-assisted solvent extraction was combined with anodic adsorptive stripping voltammetry at a gold microelectrode to extract and quantify the herbicide atrazine in spiked soil samples. A systematic study of the experimental parameters affecting the stripping response was carried out by square-wave voltammetry. The voltammetric procedure is based on controlled adsorptive accumulation of atrazine at the potential of 0.35V (versus Ag/AgCl) in the presence of Britton–Robinson buffer pH (2.0). The limit of detection obtained for a 30 sec collection time was 4.3x10-7 mol L-1. Recovery experiments, at the 1µgg-1 level of spiking, gave good results for the global procedure, and the values found were comparable to those obtained by HPLC.